2019
DOI: 10.1038/s41594-019-0250-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions underlying liquid−liquid phase separation of the FUS low-complexity domain

Abstract: The low complexity domain of the RNA-binding protein FUS (FUS LC) mediates liquid-liquid phase separation (LLPS), but interactions between the repetitive SYGQ-rich sequence of FUS LC that stabilize the liquid phase are not known in detail. By combining NMR and Raman spectroscopy, mutagenesis, and molecular simulation, we demonstrate that heterogeneous interactions involving all residue types underlie LLPS of human FUS LC. We find no evidence that FUS LC adopts conformations with traditional secondary structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

63
700
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 542 publications
(813 citation statements)
references
References 65 publications
63
700
0
Order By: Relevance
“…A second set of reports has suggested that LCDs within condensed droplets remain entirely disordered and dynamic [62][63][64][65] (Figure 2). These conclusions stem from solution NMR spectroscopy on pure dense phases.…”
Section: Structures Of Low Complexity Domains Studied In Dense Liquidmentioning
confidence: 99%
“…A second set of reports has suggested that LCDs within condensed droplets remain entirely disordered and dynamic [62][63][64][65] (Figure 2). These conclusions stem from solution NMR spectroscopy on pure dense phases.…”
Section: Structures Of Low Complexity Domains Studied In Dense Liquidmentioning
confidence: 99%
“…We find that the “bona fide” heterochromatin proteins contain various segments of high hydrophobicity and with a high fraction of charged residues (Figs A–C and EV1A–E), which could potentially favour phase separation. These features may be hard to interpret however, since they may not be sufficient per se to drive liquid–liquid phase separation, as recently shown for the FUS low‐complexity domain . Overall, these analyses suggest that the “bona fide” heterochromatin proteins that we selected have additional features linked to the potential to phase separate.…”
Section: Resultsmentioning
confidence: 84%
“…In the present study, neutral beads and empty lattice sites do not interact energetically with other beads; other types of interactions could be included. Several different types of interactions are thought to contribute to IDP phase separation, including π-π stacking (i.e., interactions between aromatic residues), cation-π, dipole-dipole interactions and hydrogen bonding [10,47]. Hydrophobic attraction is a key stabilizing force in protein folding [48] and aggregation [49], and it can also play a role in liquid-liquid phase separation [50].…”
Section: Discussionmentioning
confidence: 99%